Mapping Digital Content Needs Among Midwifery Students in Indonesia - Harridhil Silmi; Dzulfikar Djalil Lukmanul Hakim; Ari Indra Susanti; Puspa Sari; Deni K. Sunjaya; Hadi Susiarno; Qorinah Estiningtyas Sakilah Adnani; Anis Novitasari (JTP - Jurnal Teknologi Pendidikan, 2026)
Modern midwifery education demands that educators integrate technology to enhance student competency. As digital natives, midwifery students possess significant potential to leverage mobile applications. However, the specific usage patterns and the gap between available applications and priority clinical needs in Indonesia remain unmapped. Objective: This study aims to identify smartphone usage patterns and map priority digital learning material needs among midwifery students to inform curriculum enhancement. Methods: Utilizing a cross-sectional descriptive quantitative design, an online survey was conducted with 182 midwifery students in Bandung Raya, selected via convenience sampling. The instrument, evaluated for validity and reliability, measured demographics, device usage, and priority learning needs. Data were analyzed using descriptive frequency statistics. Results: All respondents (100%) owned smartphones, with 76.92% actively using them for learning, primarily favoring e-learning applications (80.22%). Crucially, the study identified a significant demand for digital content focused on patient communication (76.37%) and pregnancy care (27.47%), revealing a clear gap between students' high technological readiness and the availability of targeted clinical modules. Conclusion: Smartphones are essential, yet their specific clinical potential remains underutilized. To enhance the midwifery curriculum, institutions must employ established instructional design frameworks to develop targeted, interactive digital learning modules that directly address the identified high-priority clinical skills, thereby bridging the gap between digital readiness and professional competency.